EFEKTIVITAS PENGGUNAAN BUKU KIA DENGAN E-BOOK TENTANG PENGETAHUAN GIZI IBU HAMIL DI PUSKESMAS PUTRI AYU - Bessek Syahdila; Suryani Suryani; Herinawati Herinawati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Pregnant women are a group that is most vulnerable to nutritional problems because it can affect the growth and development of the fetus they contain. Nutrition of pregnant women is an important thing that must be met during pregnancy. The purpose of this study is the effectiveness of the use of MCH books compared to ebooks on nutritional knowledge of pregnant women at Putri Ayu Health Center in 2022. This study is a quantitative study using a "Quasy Experimental Pre-Post Test With Control Group" research design. The population in this study were all pregnant women who were at the Putri Ayu Health Center in 2022 January-February with a total of 57 people. The sample is 50 respondents. The sampling technique used is purposive sampling. The results showed that the MCH book was more effective than the ebook on the knowledge of pregnant women at the Putri Ayu Health Center in 2022 with a difference in effectiveness of 2.04. It is recommended for all pregnant women to be able to have a MCH handbook so that information related to pregnancy is maximized